2001
DOI: 10.1385/mb:17:3:193
|View full text |Cite
|
Sign up to set email alerts
|

A Plasmid Cloning Vector with Precisely Regulatable Copy Number in Escherichia coli

Abstract: We have developed a genetic system allowing for precise regulation of plasmid copy number in Escherichia coli cells. A cloning vector based on this system is described in this article. The pTC lambda 3 plasmid is a lambda replicon, but transcription controlling initiation of plasmid DNA replication starts from the PtetA promoter instead of phage lambda PR promoter. Additionally, activity of PtetA promoter is negatively controlled by the TetR repressor whose gene is located on the same plasmid vector and is ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It was shown in numerous subsequent studies that the cII and the cro regulatory loops are not essential for λ plasmid replication; transcription from the p o promoter seems important but not the transcript, oop RNA (for details, see Taylor & Wegrzyn, 1995). Finally it was shown that p R can be replaced by a different (inducible) promoter (Herman‐Antosiewicz et al , 2001), which relieves λ plasmid replication from the intricate control by host DnaA (Glinkowska et al , 2003). These results led to the functional definition of the λ‐type replication module being composed of the O ( ori λ) and P genes (Wrobel & Wegrzyn, 2002).…”
Section: Bacteriophage Replication Modulesmentioning
confidence: 99%
“…It was shown in numerous subsequent studies that the cII and the cro regulatory loops are not essential for λ plasmid replication; transcription from the p o promoter seems important but not the transcript, oop RNA (for details, see Taylor & Wegrzyn, 1995). Finally it was shown that p R can be replaced by a different (inducible) promoter (Herman‐Antosiewicz et al , 2001), which relieves λ plasmid replication from the intricate control by host DnaA (Glinkowska et al , 2003). These results led to the functional definition of the λ‐type replication module being composed of the O ( ori λ) and P genes (Wrobel & Wegrzyn, 2002).…”
Section: Bacteriophage Replication Modulesmentioning
confidence: 99%
“…Differences in the copy number of the plasmids because of their unique origin of replication will have implications to the expression of the gene [18] . One would like to believe that increasing the copy number of a plasmid would lead to increased gene dosage [ 4 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids pKB2 (Kur et al ., 1987) and pCB104 (Boyd and Sherratt, 1995) are standard λ plasmids bearing a replication region of bacteriophage λ and a kanamycin resistance and a chloramphenicol resistance gene respectively. Plasmid pTCλ3 is a λ replicon bearing the p tet promoter instead of p R (Herman‐Antosiewicz et al ., 2001). For its replication in host cells, pTCλ3 requires stimulation of the p tet promoter by the addition of an inductor, autoclaved chlortetracycline, to a culture medium (for details, see Herman‐Antosiewicz et al ., 1998a,b; 2001; Herman‐Antosiewicz and Wegrzyn, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pTCλ3 is a λ replicon bearing the p tet promoter instead of p R (Herman‐Antosiewicz et al ., 2001). For its replication in host cells, pTCλ3 requires stimulation of the p tet promoter by the addition of an inductor, autoclaved chlortetracycline, to a culture medium (for details, see Herman‐Antosiewicz et al ., 1998a,b; 2001; Herman‐Antosiewicz and Wegrzyn, 1999). Plasmid pR‐HG (Szalewska‐Palasz et al.…”
Section: Methodsmentioning
confidence: 99%